Analysis of the Roles and the Dynamics of Breathy and Whispery Voice Qualities in Dialogue Speech. (4th January 2010) - Ishi, Carlos Toshinori; Ishiguro, Hiroshi; Hagita, Norihiro
Abstract : Breathy and whispery voices are nonmodal phonations produced by an air escape through the glottis and may carry important linguistic or paralinguistic information (intentions, attitudes, and emotions), depending on the language. Analyses on spontaneous dialogue speech utterances of several speakers show that breathy and whispery voices are related with the expression of a variety of emotion- or attitude-related paralinguistic information. Potential acoustic parameters for characterizing breathy/whispery segments are introduced and used to describe the dynamics of breathiness along the utterances in different paralinguistic items.